Penerapan Restorative Justice di Daerah dalam Kerangka Negara Hukum Di Desa Mulur Kecamatan Bendosari - Asri Agustiwi (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2025)
The goal of this community service program is to provide knowledge about the application of restorative justice in the region within the framework of a rule of law, where the criminal justice system in Indonesia is currently still dominated by a retributive approach, which focuses on punishment and revenge against offenders of criminal acts. This approach often receives criticism due to the lack of attention to the recovery of victims and the social reintegration of offenders. This has encouraged the search for alternative resolutions to criminal acts that are more humane and focused on recovery, yet still within a legal framework. One alternative that has gained a lot of attention in recent years is restorative justice (restorative justice). Restorative justice is a problem-solving method through deliberation. This approach emphasizes the restoration of relationships between the offender and the victim, as well as the social reintegration of the offender. Restorative justice views criminal acts as violations of social relationships, rather than merely violations of the law. However, the issues faced by the community regarding the implementation of Restorative Justice in the area are still very unfamiliar, with many people not yet knowing or understanding it. Through this socialization, it was found that the community is capable of understanding the procedures for resolving disputes through community leaders using restorative justice. Keywords: Restorative Justice, Rule of Law, Mulur Village